"Every One of Them Are Worth It": Blanche Van Leuven Browne and the Education of the "Crippled Child". (August 2020) - Duncan, Leanna
Abstract : Many rights struggles have promoted education and learning as proof of citizenship and capacity, and disability rights movements are no exception. Blanche Van Leuven Browne, one early twentieth-century polio survivor, reimagined the possibilities of education for "crippled children" by approaching schooling as not only preparation for vocational work but as a sign of disabled children's social worthiness. This article explores the role of education in Browne's life and work, from her childhood in the 1880s to the Detroit hospital-school for physically disabled children she operated from 1907 to 1918. Browne's educational approach emphasized writing and citizenship to (re)define the identity of the "crippled child, " envisioning each as an intelligent future citizen. This approach contrasted with predominant contemporary medical, philanthropic, and educational approaches, which emphasized medical care and vocational training for children with orthopedic disabilities. It also distanced physically disabled children from intellectually disabled children, who were key cultural targets of eugenic fears.